1997
DOI: 10.1139/h97-036
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of a Mathematical Model to Predict 10-km Performance From the Conconi Test and Ventilatory Threshold Measurements

Abstract: The purpose of this study was to validate a mathematical model (MM) that evaluates the Conconi test and predicts 10-km race time. In addition, the relationship between ventilatory threshold (Tvent) determined from a laboratory test and heart rate deflection (HRd) from the Conconi test were examined. Seventeen trained runners performed the Conconi test, and performance times were predicted using a MM based on a logistics function. A correlational analysis indicated a highly significant relationship (r = .98, p … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 16 publications
0
18
0
1
Order By: Relevance
“…An analogous association of _ Vo 2 def and lactate threshold was demonstrated by Bickham et al (5) in runners. Several studies have established that HRdef is also associated with the activation of the anaerobic mechanisms (8,9,13,14,23,38). Only in the study by Carey (12) was this association not demonstrated.…”
Section: Discussionmentioning
confidence: 97%
“…An analogous association of _ Vo 2 def and lactate threshold was demonstrated by Bickham et al (5) in runners. Several studies have established that HRdef is also associated with the activation of the anaerobic mechanisms (8,9,13,14,23,38). Only in the study by Carey (12) was this association not demonstrated.…”
Section: Discussionmentioning
confidence: 97%
“…The increase of the maximum HR and the maximum cardiac debt itself identified in exercise under hyperoxia, and the inverse response, under laboratory induced-hyperoxia, is an evidence for this hypothesis. On the other hand, the increase of the HR during physical exercise has been commonly attributed to the increase of the metabolic demand imposed by the task's intensity (6)(7) . However, during the 10 km, the HR had its first significant increase only from the seventh lap (approximately 12 minutes) and remained high until the end of the test, while the highest υ _ was detected in the beginning of the run, followed by an expressive reduction in the simulation According to Achten and Jeukendrup (5) , the HR response during the physical exercise can also be influenced by various extrinsic factors, among them, the environmental temperature and the hydration of the individuals.…”
Section: Ementioning
confidence: 99%
“…Moreover, it is believed that independently of the aptitude level of the individuals, the heart rate (HR) is the main responsible for the increase of the cardiac debt in the intensities between 60% and 70% of the maximum oxygen consumption (4) . Therefore, the results of some studies pointed to the possibility of the use of the monitoring of the HR to represent the physiological demand in tasks predominantly aerobic (5)(6)(7) . Besides the HR, the scale of perceived exertion (PE) presented by Borg (8) has also been widely used in the control (9)(10) and in the indirect determination of fulfillment of continuous cycle tasks (11) and intermittent (12) with aerobic predominance.…”
Section: Introductionmentioning
confidence: 99%
“…Foi identificado um aumento não linear da relação FC/CTC, com a presença de um ponto de deflexão da FC (PDFC), posteriormente, associado ao segundo limiar de lactato 5 . Por apresentar um baixo custo e não requerer técnicas invasivas 6,7 , o PDFC, frequentemente identificado de forma visual, passou a ser amplamente utilizado por técnicos e treinadores para estimativa do segundo limiar de transição metabólica 8 . Evidências também foram descritas quando analisada a porção inferior da curva FC/CTC 9,10 .…”
Section: Introductionunclassified